PEMENUHAN KEBUTUHAN CAIRAN DAN STATUS HIDRASI SETELAH LATIHAN PADA ATLET RENANG DI KOTA SEMARANG - Yurizka, Berta; Widajanti, Laksmi; Kartasurya, Martha Irene (Jurnal Kesehatan Masyarakat (Undip), 2017)
Swimmers were potential to be dehydrated because their brain can not detect the dehydration properly during exercise. Dehydration can significantly increase fatigue and decrease athletic performance, physically and mentally. The objective of this study was to analyze the relationship between fluid intake and hydration status among swimmers in Semarang City. The study was an explanatory research with a cross sectional approach. The number of respondents were 30 children athletes aged 7 to 12 years old in Tri Çakti Semesta Club, Semarang. Subjects were selected by total sampling method and data were analyzed by Rank Spearman tests. The results showed that the average energy adequacy level was 89.71±24.15 %, fluid adequacy level (75.3±8.7)%, body fat percentage were 24.5±7.72% for males and body fat percentage were 20.2±5.19 % for females. The average physical activity level was 1.82±0.13 PAL. Fluid intake correlated to hydration status level were (r=-0,718;p=0.001). Energy adequacy was not related with hydration status after exercise (p=0,275). There is no correlation between body temperature, body fat percentage and physical activity to hydration status, so they were not confounding variables in this research. It is recommended for athletes parents and coaches to be more concern about athlete fluid consumption for a better health and athlete achievement .